Die affektiewe funksionering van jong werkende egpare - Slabbert, Anna Maria Elizabeth (University of the Free State, 1999)
Abstract not available
Keywords: Marriage -- Psychological aspects; Communication in marriage; Interpersonal relations; Thesis (Ph.D. (Psychology))--University of the Orange Free State, 1999